Effects of 5-year experimental warming in the Alpine belt on soil Archaea: Multi-omics approaches and prospects - D'Alò, Federica; Zucconi, Laura; Onofri, Silvano; Canini, Fabiana; Cannone, Nicoletta; Malfasi, Francesco; Morais, Daniel Kumazawa; Starke, Robert (Environmental microbiology reports, 2023)
We currently lack a predictive understanding of how soil archaeal communities may respond to climate change, particularly in Alpine areas where warming is far exceeding the global average. Here, we characterized the abundance, structure, and function of total (by metagenomics) and active soil archaea (by metatranscriptomics) after 5-year experimental field warming (+1°C) in Italian Alpine grasslands and snowbeds. Our multi-omics approach unveiled an increasing abundance of Archaea during warming in snowbeds, which was negatively correlated with the abundance of fungi (by qPCR) and micronutrients (Ca and Mg), but positively correlated with soil water content. In the snowbeds transcripts, warming resulted in the enrichment of abundances of transcription and nucleotide biosynthesis. Our study provides novel insights into possible changes in soil Archaea composition and function in the climate change scenario.
Keywords: půdní mikrobiologie; multiomika; Archaea; Climate Change; Italy; Soil; Multiomics; půda; Itálie; klimatické změny; Soil Microbiology